Dinamika Keamanan dan Demokrasi di Indonesia - Huriyah, Syarifah; Hazyimara, Karunia; Zuhairah, Syarifah (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This article discusses the challenges faced by the South Sulawesi Police in the context of the dynamics of security and democracy in Indonesia ahead of the 2024 Regional Head Elections (Pilkada). The post-Cold War era and the rise of new global powers have influenced the democratization process in various countries, including Indonesia, which has experienced a significant democratic transition after the 1998 Reformation. However, this process also presents challenges such as radicalization, social polarization, and conflict that are often exploited by political actors. In the scientific oration of the South Sulawesi Police Chief at the 107th Graduation Ceremony of UIN Alauddin Makassar with the theme